Spatiotemporal variation of rainfall and its implications on water resources management: The case of Manyame River catchment in Zimbabwe. Issue 1 (23rd January 2023) - Murove, Brian; Mujere, Never; Gumindoga, Webster
Abstract: Rainfall is an important hydrometeorological variable that affects river flow regimes and the amount of water flowing into surface water bodies and underground aquifers. Changing rainfall patterns and magnitudes contribute to extreme events including floods, droughts, and landslides. Thus, understanding of rainfall distribution is vital to sound water resources planning and allocation to users. Owing to the shortage of evenly distributed of rainfall stations in the arid and semiarid catchments, satellite rainfall products are regarded as reliable alternatives. This study therefore analyzes the long‐term spatiotemporal variation of rainfall in Manyame River catchment in Zimbabwe. Monthly rainfall data spanning from 1982 to 2019 were retrieved from the Climate Hazards Group Infra‐Red Precipitation with Station (CHIRPS). In situ rainfall data obtained from the country's two Meteorological Services Department were used to determine the accuracy of satellite data. Rainfall trends were tested using the Mann–Kendall trend test. The results showed goodness of fit between in situ and remotely sensed rainfall data. There is no significant increasing and decreasing trends in quarterly, monthly, and wet season rainfall. Statistically significant decreasing trends were observed in the central parts of the catchment during the dry season. The changing rainfall trends highlight the need for integrated and adaptive water resource management strategies to avoid adverse effects of floods and droughts in the catchment. Abstract: 摘要 降雨量是一个重要的水文气象变量, 它能影响河流流态以及流入地表水体和地下含水层的水量。不断变化的降雨模式和强度对一系列极端事件作贡献, 包括洪水、干旱和山体滑坡。因此, 了解降雨分布对于合理的水资源规划和用户分配而言至关重要。由于干旱和半干旱流域缺乏均匀分布的雨量站, 卫星雨量产品被视为可靠的替代品。因此, 本研究分析了津巴布韦 Manyame 流域降雨量的长期时空差异。使用气候危害组红外降水与站点数据 (CHIRPS)检索 1982 年到 2019 年的月降雨量数据。从该国两个气象部门获得的现场降雨数据被用于确定卫星数据的准确性。使用曼‐肯德尔趋势检验测试降雨趋势。结果表明, 现场和遥感降雨数据之间的拟合度良好。季度降雨量、月降雨量和雨季降雨量均无明显增减趋势。旱季期间, 在流域中部地区观察到显著下降趋势。不断变化的降雨趋势强调, 需要综合和适应性水资源管理策略, 以避免流域洪水和干旱的不利影响。. Abstract: La lluvia es una variable hidrometeorológica importante que afecta los regímenes de flujo de los ríos y la cantidad de agua que fluye hacia los cuerpos de agua superficiales y los acuíferos subterráneos. Los patrones y magnitudes cambiantes de las lluvias contribuyen a eventos extremos, como inundaciones, sequías y deslizamientos de tierra. Por lo tanto, la comprensión de la distribución de las lluvias es vital para la buena planificación y asignación de los recursos hídricos a los usuarios. Debido a la escasez de estaciones pluviométricas distribuidas uniformemente en las cuencas áridas y semiáridas, los productos pluviométricos satelitales se consideran alternativas confiables. Por lo tanto, este estudio analiza la variación espacio‐temporal a largo plazo de las precipitaciones en la cuenca del río Manyame en Zimbabue. Los datos de lluvia mensuales que abarcan desde 1982 hasta 2019 se recuperaron de la Precipitación infrarroja con estación (CHIRPS) del Grupo de peligros climáticos. Los datos de lluvia in situ obtenidos de los dos Departamentos de Servicios Meteorológicos del país se utilizaron para determinar la precisión de los datos satelitales. Las tendencias de precipitación se probaron utilizando la prueba de tendencia de Mann‐Kendall. Los resultados mostraron bondad de ajuste entre los datos de precipitación in situ y los obtenidos por teledetección. No hay tendencias significativas de aumento y disminución en las precipitaciones trimestrales, mensuales y de la estación húmeda. Se observaron tendencias decrecientes estadísticamente significativas en las partes centrales de la cuenca durante la estación seca. Las tendencias cambiantes de las precipitaciones resaltan la necesidad de estrategias de gestión de recursos hídricos integradas y adaptables para evitar los efectos adversos de inundaciones y sequías en la cuenca.